2016
DOI: 10.1136/postgradmedj-2016-134247
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and myths that limit the use of intrauterine contraception in nulliparous women: a survey of Brazilian gynaecologists

Abstract: The three most commonly reported barriers to considering IUC as a contraceptive option for nulliparous woman were concerns about PID and difficult or painful insertion. The challenge is to ensure that gynaecologists understand the evidence and do not disregard IUC as a potential option for nulliparous women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
1
5
0
1
Order By: Relevance
“…Addressing/dispelling myths and misconceptions among youth is particularly important for future contraception use. By nature of originating in social networks as well as their likelihood to ‘stick’ indefinitely, myths and misconceptions among youth should be dispelled early to prevent their becoming engrained 6 41. Indeed, our study found that two of the three most commonly-believed myths and misconceptions among youth age 18–24 years (people who use contraceptives end up with health problems, and contraceptives can harm a woman’s womb) were also the top myths for youth and adult women aged 15–49 years in Kenya, Nigeria and Senegal 9…”
Section: Discussionmentioning
confidence: 99%
“…Addressing/dispelling myths and misconceptions among youth is particularly important for future contraception use. By nature of originating in social networks as well as their likelihood to ‘stick’ indefinitely, myths and misconceptions among youth should be dispelled early to prevent their becoming engrained 6 41. Indeed, our study found that two of the three most commonly-believed myths and misconceptions among youth age 18–24 years (people who use contraceptives end up with health problems, and contraceptives can harm a woman’s womb) were also the top myths for youth and adult women aged 15–49 years in Kenya, Nigeria and Senegal 9…”
Section: Discussionmentioning
confidence: 99%
“…The intervention group assignment, self-assessed competency score, as well as number of reported LARC procedure experiences during medical school were all associated with various skill scores. The need to improve contraception knowledge, especially LARC, among medical students has been recognized in LMICs [1][2][3][4][5][6], but without documented effective strategies. In the United States, a prospective study of students at seven medical schools found that IUD knowledge increased significantly after completion of a clinical rotation in Ob-Gyn [13].…”
Section: Discussionmentioning
confidence: 99%
“…Across the globe, accessing the most effective family planning (FP) methods, especially long-acting reversible contraceptives (LARC), requires trained providers. However, studies from low-and middle-income countries (LMICs) suggest that medical students are often unprepared to provide these services because of misconceptions or lack of training [1][2][3][4][5][6]. This training gap delays the ability to address this important women's health need.…”
Section: Introductionmentioning
confidence: 99%
“…[16,17]. Concern about insertion pain may also be a barrier for gynecologists to consider the IUD as a contraceptive option, especially for nulliparous women [18].…”
Section: Introductionmentioning
confidence: 99%